Potencial evocado auditivo P300 na avaliação cognitiva de idosos vivendo com HIV/AIDS - João Luiz Cioglia Pereira Diniz (2016)
The ageing of people living with HIV has been associated with higher frequency of neurocognitive disorders. The auditory evoked potentials P300 evaluate cognitive function. We analyzed auditory cognition of elderly with HIV through P300. We compared 34 HIV-infected elderly undergoing regular treatment to 80 HIV-negative elderly healthy controls in relation to P300 latency and the scores of neuropsychological tests. The groups were stratified into the age subgroups: 5059, 6069 and 70 years. Each age subgroup infected by HIV was compared to the age subgroup of controls that was one level of age older. The HIV group consisted of 20(61%) men, mean age 61±7 years and the controls of 24(32%) men, mean age 67±4 years. Years of schooling were seven (interquartile range [IR] 4/8) in HIV group against four (IR 4/11) in controls (p=0.044). P300 latency was similar between genders in the groups. P300 latency was 353±35 ms in HIV group and 331±29 ms in controls (p=0.006). Inwithin-analysis, P300 latency augmented with increasing age in HIV group (p=0.001) and remained stable in controls (p=0.252). In between-analysis, P300 latency was delayed in HIV subgroup 6069 as compared to controls 70 years (p=0.033) and delayed in HIV subgroup 70 years as compared to controls 70 years (p<0.001). In neuropsychological tests, HIV group presented poor performance in Nine Hole test (p=0.029) and correlation was found between dominant hand performance and P300 delay (p=0.043). We concluded that even under regular treatment, HIV infection may accelerate the cognitive impairment related to ageing.